Smartwatch-Based Information System as a Compliance Detector in Traffic - Adi Rizal Rizkulloh; Bramasta Bramasta; Risky Pratama (Universitas Komputer Indonesia, 2023)
The purpose of this study is to design a mobile-based application that serves to provide reminders to vehicle users to create orderly traffic and aims to build an obedient attitude to applicable traffic rules. To support this research, we used a qualitative method. While in the application development process using the Prototype approach. The results of this study indicate that the development of this system can increase compliance in traffic and reduce the number of accidents so that an orderly traffic can be created. The main concept of this system is as a reminder so that drivers are orderly traffic, for example, when a driver commits a violation by driving on the wrong road, he will get a reminder. This information system will later get a warning signal that will be sent to the smartwatch when the user violates traffic, the user will be aware of things that endanger his life or others.